Respostas
respondido por:
1
y² - 2y -3y + 6 = 0
y² -5y + 6 = 0
Δ = 25 - 4(1)(6) = 25 - 24 = 1
√Δ = 1
y1 = (5 + 1)/2 = 3
y2 = (5 - 1)/2 = 2
Resposta: 6 e 3 não são raízes da equação. As raízes são 2 e 3
Espero ter ajudado
y² -5y + 6 = 0
Δ = 25 - 4(1)(6) = 25 - 24 = 1
√Δ = 1
y1 = (5 + 1)/2 = 3
y2 = (5 - 1)/2 = 2
Resposta: 6 e 3 não são raízes da equação. As raízes são 2 e 3
Espero ter ajudado
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás